Athletes' experiences, enjoyment, satisfaction, and memories from the Extreme Sport Week in Voss, Norway. Issue 4 (20th August 2014) - Mykletun, Reidar Johan; Rumba, Maira
Abstract : Purpose: The study demonstrates how experiences, sport careers, and biographic variables predict: enjoyment, satisfaction, and memories from the unique and spectacular Extreme Sport Week (Ekstremsportveko), Voss, Norway, as reported by of the extreme sport athletes Design/methodology/approach: An electronic questionnaire was distributed to all participants during 2011, and collected responses from 292 athletes (27 percent response rate). Data were analysed by frequencies, mean values, correlations, and multiple regression. Findings: Extreme sport athletes were typically amateurs with serious leisure careers. Social ties between participants and volunteers were found. They had positive experiences at the event, and the realms of education, aesthetics and entertainment were the strongest predictors of enjoyment, satisfaction and memories. Level of excitement augmented the explained variance, especially when predicting memories. Most participants intended to re-visit future Extreme Sport Weeks. Research limitations/implications: The moderate response rate warrants generalisations from the study. As the study is cross-sectional, cause-effect relationships cannot be established. Practical implications: For event organisers, the study shows the athletes' appreciations with its managerial implications. Originality/value: This study is the first to explore the experiences of athletes who participated in the unique and spectacular event Extreme Sport Week. For researchers and practitioners, it is an example of how to measure experiences and their outcomes of (extreme sport) events.